2017
DOI: 10.1123/jtpe.2017-0034
|View full text |Cite
|
Sign up to set email alerts
|

Relatedness Need Satisfaction, Intrinsic Motivation, and Engagement in Secondary School Physical Education

Abstract: Purpose:Using self-determination theory, this study examined unique contributions of relatedness need satisfaction (to both teachers and peers) to intrinsic motivation and engagement (behavioral, cognitive, and emotional) over and above those of autonomy need satisfaction and competence need satisfaction among Turkish students in secondary school physical education.Method:Participants were 331 (162 boys, 169 girls) middle and high school students enrolled in physical education classes at four public schools in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 13 publications
2
25
0
1
Order By: Relevance
“…The results also showed that the thwarting of psychological needs negatively predicted autonomous motivation, whereas the satisfaction of psychological needs positively predicted autonomous motivation. These results are similar to multiple previous studies [42,50,51], where feeling confident and competent during class exercises, feeling integrated and a good interpersonal relationships with classmates and/or with the teacher, feeling ownership of one’s own destiny, and participating in original activities helps adolescents to feel an autonomous motivation towards PE classes [52]. Following this, autonomous motivation positively predicted healthy eating habits and the practice of physical activity and negatively predicted unhealthy eating habits.…”
Section: Discussionsupporting
confidence: 94%
“…The results also showed that the thwarting of psychological needs negatively predicted autonomous motivation, whereas the satisfaction of psychological needs positively predicted autonomous motivation. These results are similar to multiple previous studies [42,50,51], where feeling confident and competent during class exercises, feeling integrated and a good interpersonal relationships with classmates and/or with the teacher, feeling ownership of one’s own destiny, and participating in original activities helps adolescents to feel an autonomous motivation towards PE classes [52]. Following this, autonomous motivation positively predicted healthy eating habits and the practice of physical activity and negatively predicted unhealthy eating habits.…”
Section: Discussionsupporting
confidence: 94%
“…In the case of ego climate, the most influential indicator for boys is punishment for mistakes, whereas for girls it is unequal recognition. These data are in line with the results of studies by Bandeira et al [ 47 ] and Xiang et al [ 53 ], which indicate that effort and improvement constitute the fundamental factor characterizing the type of motivation that is more self-determined or intrinsic, its focus being on improving and developing skills rather than thinking about external rewards. Since boys are more ego-oriented than girls, they are more concerned about punishment, whereas girls are influenced to a greater extent by unequal recognition, worrying less than boys about punishment and focusing more on intrinsic goals [ 49 , 51 ].…”
Section: Discussionsupporting
confidence: 92%
“…This is associated with the promotion of social relations, since tasks are proposed that encourage both individual and group achievement with others [ 73 ]. This pedagogical model seeks to generate the intrinsic motivation of the student [ 74 ], posing tasks that represent attractive challenges for the students. Thus, and under the orientation of achievement towards the task, transferability and trans-contextual analysis of the learning generated is sought [ 75 ].…”
Section: Origins Of the Attitudinal Stylementioning
confidence: 99%